Outcomes of an outpatient home-based prehabilitation program before pancreaticoduodenectomy: a retrospective cohort study - Chan, Kai Siang (2023)
Backgrounds/Aims: Prehabilitation aims for preoperative optimisation to reduce postoperative complications. However, there is a paucity of data on its use in patients undergoing pancreaticoduodenectomy (PD). Thus, this study aims to evaluate the outcomes of a home-based outpatient prehabilitation program (PP) versus no-PP in patients undergoing PD. Methods: This retrospective cohort study compared patients who underwent PP versus no-PP before elective PD from January 2016 to December 2020. Inclusion criteria for PP were < 65 years or 65–74 years with FRAIL score < 3. No-PP included dietician, case manager and anesthesia review. PP included additional physiotherapy sessions, caregiver training and interim phone consultation. Univariate and multivariate analysis were used to evaluate length of stay (LOS), morbidity, 30-day readmission, and 90-day mortality. Results: Seventy-one patients (PP: n = 50 [70.4%]; no-PP: n = 21 [29.6%]) were included in this study. Median age was 65 years (inter-quartile range [IQR]: 58–72 years). Majority (n = 58 [81.7%]) of patients underwent open surgery. Ductal adenocarcinoma was the most common histology (49.3%). Patient demographics were comparable between both groups. Overall median LOS was 11.0 days (IQR: 8.0–17.0 days). Compared to no-PP, PP was not independently associated with reduced intra-abdominal collections (odds ratio [OR]: 0.43; 95% confidence interval [CI]: 0.03–6.11, p = 0.532), major morbidity (OR: 1.31; 95% CI: 0.09–19.47; p = 0.845) or 30-day readmission (OR: 3.16; 95% CI: 0.26–38.27; p = 0.365). There was one (1.4%) 30-day mortality. Conclusions: Our outpatient PP with unsupervised exercise regimes did not improve postoperative outcomes following elective PD.